1983
DOI: 10.1007/bf00330892
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the region of rDNA involved in polytenization in salivary glands of Drosophila hydei

Abstract: During the formation of polytene chromosomes in salivary glands of Drosophila hydei, the genes for ribosomal RNA (rDNA) are underreplicated relative to the rest of the genome. We have measured the number of rRNA genes with and without intervening sequences (ivs+ and ivs- genes) in polytene chromosomes of different genotypes. In the group of genotypes having a large number of ivs- rRNA genes polytenization only occurs within the cluster of ivs- genes. In each of these genotypes rDNA polytenization reaches a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…All D. hydei strains used in this study have been used previously for rDNA work and are named for the X and Y chromosomes. Strain bb' (bbl/bbl x bb'/Y) carries a bobbed X chromosome; strain X7 (X7/X7 x X7/Y) is a subline ofthe Dusseldorfwild-type strain; strain X X/Y (XAX/Y x X/Y) females carry a compound X chromosome that has no rDNA (14). Strain wml/Y (wml/Y x X-3/Y) females have a compound X chromosome (wml); males carry a X-autosome 3 translocation that has no rDNA (15).…”
Section: Methodsmentioning
confidence: 99%
“…All D. hydei strains used in this study have been used previously for rDNA work and are named for the X and Y chromosomes. Strain bb' (bbl/bbl x bb'/Y) carries a bobbed X chromosome; strain X7 (X7/X7 x X7/Y) is a subline ofthe Dusseldorfwild-type strain; strain X X/Y (XAX/Y x X/Y) females carry a compound X chromosome that has no rDNA (14). Strain wml/Y (wml/Y x X-3/Y) females have a compound X chromosome (wml); males carry a X-autosome 3 translocation that has no rDNA (15).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have established that, at the level of the total polyploid tissue DNA, the overall contribution of the two NOs to the polyploidization of the rDNA is a function of the pair of NOs examined (6,(8)(9)(10)(11)(12). In some cases, one NO is replicated to the virtual exclusion of the other, whereas for other NO pairs, cistrons from both NOs are equally well represented in the total polyploid tissue DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying this independent regulation of rDNA polyploidization are not understood but the studies of Spear and Gall (2, 3) have established that in polytene salivary gland tissue, the rDNA is autonomously replicated to a constant level that is independent of both the amount of rDNA initially present in the diploid genome and the number of nucleolar organizer (NO) regions within the genome in which this rDNA is distributed. It has been suggested that endoreplication of rDNA cistrons from only one NO may in part explain these observations (1, 5-7).Recent studies have established that, at the level of the total polyploid tissue DNA, the overall contribution of the two NOs to the polyploidization of the rDNA is a function of the pair of NOs examined (6,(8)(9)(10)(11)(12). In some cases, one NO is replicated to the virtual exclusion of the other, whereas for other NO pairs, cistrons from both NOs are equally well represented in the total polyploid tissue DNA.…”
mentioning
confidence: 99%
“…AU D. hydei strains used in this study have been used previously for rDNA work and are named for the X and Y chromosomes. Strain bb' (bb'/bb' x bb'/Y) carries a bobbed X chromosome; strain X 7 (X 7 /X 7 x X 7 /Y) is a subline of the Düsseldorf wild-type strain; strain X"X/Y (X'X/Y x X/Y) females carry a compound X chromosome that has no rDNA (14). Strain wml/Y (wml/Y x X-3/Y) females have a compound X chromosome iyvml); males carry a X-autosome 3 translocation that has no rDNA (15).…”
Section: Methodsmentioning
confidence: 99%
“…The transposon Minos was discovered in the rDNA of Drosophila hydei (14) It is ^ 1.8 kbp with long (254 bp) inverted terminal repeats. The Minos element contains two nonoverlapping open reading frames separated by a putative intron and coding for a conceptual polypeptide that shows >40% sequence identity with the Tel transposase of the nematode Caenorhabditis elegans (15).…”
Section: Noti Noti Ecorimentioning
confidence: 99%